Destructive and non-destructive testing of samples from PLA and PETG materials. Issue 1 (November 2021) - Balint, T; Živčák, J; Hudák, R; Tóth, T; Kohan, M; Lancoš, S
Abstract: This study deals with the properties of PLA and PETG materials, which are important for gaining knowledge in biomedical applications. The process of obtaining an ideal implant from a material with suitable mechanical and physical properties is a complex process considered to be one of the most difficult in tissue engineering. PLA and PETG material properties were determined based on performed non-destructive and destructive materials testing methods. Destructive testing was performed on Hegewald and Peschke equipment and non-destructive testing was performed on Carl Zeiss Metrotome 1500 (Germany). Commercial filaments from various companies were selected, from which type 5A dogbone samples were printed on a TRILAB printer. Subsequently, after carrying out the tests on dogbone samples, the results were evaluated and compared with the help of graphs and tables.